2013
DOI: 10.1177/197140091302600404
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cerebral Blood Volume Measurements by Perfusion-Weighted Magnetic Resonance Imaging and Two-Year Progression-Free Survival in Gliomas

Abstract: SUMMARY -Our goal was to determine whether relative cerebral blood volume (rCBV) can serve as an adjunct to histopathologic grading in the assessment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
(49 reference statements)
2
15
0
Order By: Relevance
“…Second, relative cerebral blood flow and tumor perfusion influence tracer delivery (and consequently the amount and speed of tumoral tracer uptake) and subsequent washout after intracellular accumulation of the unbound amino acid analag, which is not incorporated into proteins and may therefore not be trapped intracellularly (15). An earlier TTP min may therefore reflect a higher amino acid transporter expression or higher tumor perfusion, which would be in line with the results of other studies reporting that tumor perfusion has prognostic significance (32)(33)(34). Although a recent study claimed that the descending part of the time-activity curves of 18 F-FET uptake does not correlate with perfusion parameters in perfusion-weighted MR imaging, the study found a high correlation with the slope of the increasing part of the time-activity curves (35), indicating that tumor perfusion does have an influence to some extent.…”
Section: Discussionsupporting
confidence: 79%
“…Second, relative cerebral blood flow and tumor perfusion influence tracer delivery (and consequently the amount and speed of tumoral tracer uptake) and subsequent washout after intracellular accumulation of the unbound amino acid analag, which is not incorporated into proteins and may therefore not be trapped intracellularly (15). An earlier TTP min may therefore reflect a higher amino acid transporter expression or higher tumor perfusion, which would be in line with the results of other studies reporting that tumor perfusion has prognostic significance (32)(33)(34). Although a recent study claimed that the descending part of the time-activity curves of 18 F-FET uptake does not correlate with perfusion parameters in perfusion-weighted MR imaging, the study found a high correlation with the slope of the increasing part of the time-activity curves (35), indicating that tumor perfusion does have an influence to some extent.…”
Section: Discussionsupporting
confidence: 79%
“…We have included only astrocytomas (anaplastic and GBM) to have a more homogeneous sample, as oligodendrogliomas are known to have different perfusion characteristics, which could bias DCE perfusion analysis [36, 37]. We used histogram analysis instead of the hot-spot ROI maximum value method.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional imaging characteristics of GBM, including location, size, and degree of enhancement; necrosis; and extent of edema, have been studied for prediction of survival. [9][10][11][29][30][31][32][33][34][35][36] Although contrast enhancement is generally used to estimate the extent of the tumor, it is clear from the literature that conventional radiologic findings, such as the absence of contrast enhancement, are not only poor predictors of tumor grade but may or may not be prognostic factors for either survival or progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Conventional MR imaging is widely used as the technique of choice for GBM diagnosis and also has an important role in monitoring disease progression and response to therapy for patients with GBM. Additional advanced imaging techniques, such as relative cerebral blood volume (rCBV) obtained from dynamic susceptibility contrast perfusion imaging, have been used to predict glioma grade [9][10][11] and assess treatment response. 12 A recent report 10 indicated that maximum relative cerebral blood volume (rCBV max ) can be used as a predictive marker of progression-free survival in patients with gliomas, regardless of the tumor grade.…”
mentioning
confidence: 99%
See 1 more Smart Citation